MANUSIA DAN DUNIA: KONSEP KRISTOLOGI DENGAN PERSPEKTIF REFORMED - Suryowati Wang (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2020)
Humans are special creatures of God with their true nature as guardians of the earth. The purpose of writing to find answers about human meaning, the meaning of the world, and how human relationships and their world? The study uses qualitative methods with a philology approach. The results of the study are: (1) man is not just a creation, he is also a person. Being a person means being able to make decisions, set goals, and move towards those goals. Humans are not robots whose actions are determined by forces outside themselves. To be one person means to be a "creation that has a choice". (2) the world is: First, in the perspective of the Bible is "creation", the whole existence of a place in which humans live with all the good blessings of God. Second, from a perspective outside the Bible, the world is identified with all sources of evil, containing: evil, bad, negative and imperfections. (3) the relationship between humans and the world is that humans must be missionaries in a Christological framework that has the duty to serve in the world as a source of evil. Humans become the "salt" and "light" of Christ fighting the source of evil.            AbstrakManusia adalah makhluk ciptaan Allah yang istimewa dengan hakekat sejatinya sebagai pemelihara bumi. Tujuan penulisan menemukan jawaban tentang makna manusia, makna dunia, dan bagaimanakah hubungan manusia dan dunianya? Penelitian menggunakan metode kualitatif  dengan pendekatan filologi. Hasil penelitian adalah: (1) manusia adalah bukan sekedar hanya ciptaan, ia juga satu pribadi. Menjadi suatu pribadi berarti mampu membuat keputusan, menetapkan tujuan, dan bergerak ke arah tujuan-tujuan itu. Manusia bukan robot yang tindakannya ditentukan oleh kekuatan di luar dirinya. Menjadi satu pribadi berarti menjadi “ciptaan yang memiliki pilihan”. (2) dunia adalah: Pertama, dalam perspektif Alkitab adalah  “tata cipta”, seluruh keberadaan tempat yang di dalamnya manusia hidup dengan segala berkat yang baik dari Allah. Kedua, dalam perspektif di luar Alkitab, dunia  adalah diidentikkan segala sumber kejahatan, berisi: hal-hal yang jahat, buruk, negatif dan ketidaksempurnaan. (3) hubungan manusia dan dunia adalah manusia mesti menjadi misioner dalam kerangka pikir Kristologi yang mempunyai tugas untuk melayani di dunia sebagai tempat sumber kejahatan. Manusia menjadi “garam” dan “terang” Kristus memerangi sumber kejahatan..